Downwash airflow field distribution characteristics and their effect on the spray field distribution of the DJI T30 six-rotor plant protection UAV - Zhang, Haiyan; Wen, Sheng; Chen, Chunling; Liu, Qi; Xu, Tongyu; Chen, Shengde; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2023)
Spray characteristics are the fundamental factors that affect droplet transportation downward, deposition, and drift. The downwash airflow field of the Unmanned Aviation Vehicle (UAV) primarily influences droplet deposition and drift by changing the spray characteristics. This study focused mainly on the effect of the downwash airflow field of the UAV and nozzle position on the droplet spatial distribution and velocity distribution, which are two factors of spray characteristics. To study the abovementioned characteristics, computational fluid dynamics based on the lattice Boltzmann method (LBM) was used to simulate the downwash airflow field of the DJI T30 six-rotor plant protection UAV at different rotor rotational speeds (1000-1800 r/min). A particle image velocimetry system (PIV) was utilized to record the spray field with the downwash airflow field at different rotational speeds of rotors (0-1800 r/min) or different nozzle positions (0, 0.20 m, 0.35 m, and 0.50 m from the motor). The simulation and experimental results showed that the rotor downwash airflow field exhibited the ‘dispersion-shrinkage-redispersion’ development rule. In the initial dispersion stage of rotor airflow, there were obvious high-vorticity and low-vorticity regions in the rotor downwash airflow field. Moreover, the low-vorticity region was primarily concentrated below the motor, and the high-vorticity region was mainly focused in the middle area of the rotors. Additionally, the Y-direction airflow velocity fluctuated at 0.4-1.2 m under the rotor. When the rotor airflow developed to 3.2 m below the rotor, the Y-direction airflow velocity showed a slight decrease. Above 3.2 m from the rotor, the Y-direction airflow velocity started to drastically decrease. Therefore, it is recommended that the DJI T30 plant protection UAV should not exceed 3.2 m in flight height during field spraying operations. The rotor downwash airflow field caused the nozzle atomization angle, droplet concentration, and spray field width to decrease while increasing the vortex scale in the spray field when the rotor system was activated. Moreover, the increase in rotor rotational speed promoted the abovementioned trend. When the nozzle was installed in various radial locations below the rotor, the droplet spatial distribution and velocity distribution were completely different. When the nozzle was installed directly below the motor, the droplet spatial distribution and velocity distribution were relatively symmetrical. When the nozzle was installed at 0.20 m and 0.35 m from the motor, the droplets clearly moved toward the right under the induction of stronger rotor vortices. This resulted in a higher droplet concentration in the right-half spray field. However, the droplet moved toward the left when the nozzle was installed in the rotor tip. For four nozzle positions, when the nozzle was installed at 0 or 0.20 m from the motor, the droplet average velocity was much higher. However, the droplet average velocity was slower when the nozzle was installed in the other two positions. Therefore, it is recommended that the nozzle is installed at 0 or 0.20 m from the motor. The research results could increase the understanding of the downwash airflow field distribution characteristics of the UAV and its influence on the droplet spatial distribution and velocity distribution characteristics. Meanwhile, the research results could provide some theoretical guidance for the choice of nozzle position below the rotor.Keywords: downwash airflow, spray field distribution, plant protection, UAV, characteristicsDOI: 10.25165/j.ijabe.20231602.8094Citation: Zhang H Y, Wen S, Chen C L, Liu Q, Xu T Y, Chen S D, et al. Downwash airflow field distribution characteristics and their effect on the spray field distribution of the DJI T30 six-rotor plant protection UAV. Int J Agric & Biol Eng, 2023; 16(2): 10-22.